Impacts of an urban toll on pollution and road accidents: evidence from São Paulo - Dias, Matheus Rezende (2023)
In this paper, we investigate the effects of an urban toll on road accidents and pollution in Sao Paulo. Using the Origin and Destination (OD) database for 2017, we employ a Nested Logit model to estimate transportation demand in Sao Paulo. Our goal is to analyze the changes in demand resulting from the imposition an urban toll of R$ 0.47 per traveled kilometer in Sao Paulo Expanded Center. Ad- ditionally, we explore the impact of the toll on Consumer Surplus, as well as on pollution and accident externalities. Our findings reveal that the urban toll per traveled kilometer can significantly reduce the number of individuals opting for car mode, decreasing its share from 33.1% to 23.9%. This reduction in car usage enables us to estimate the total pollution that can be avoided by considering the vehicle emission factors. Finally, utilizing the social cost of pollution and accidents, we calculate that the implementation of the urban toll could lead to a social gain of R$ 153 million annually.